Metagenomic Identification of Fusarium solani Strain as Cause of US Fungal Meningitis Outbreak Associated with Surgical Procedures in Mexico, 2023 - Charles Y. Chiu; Venice Servellita; Mikael de Lorenzi-Tognon; Patrick Benoit; Nanami Sumimoto; Abiodun Foresythe; Filipe M. Cerqueira; Natalie Williams-Bouyer; Ping Ren; Lauren Nicholas S. Herrera; David C. Gaston; Leanna Sayyad; et al. (Emerging Infectious Diseases)
We used metagenomic next-generation sequencing (mNGS) to investigate an outbreak of Fusarium solani meningitis in US patients who had surgical procedures under spinal anesthesia in Matamoros, Mexico, during 2023. Using a novel method called metaMELT (metagenomic multiple extended locus typing), we performed phylogenetic analysis of concatenated mNGS reads from 4 patients (P1–P4) in parallel with reads from 28 fungal reference genomes. Fungal strains from the 4 patients were most closely related to each other and to 2 cultured isolates from P1 and an additional case (P5), suggesting that all cases arose from a point source exposure. Our findings support epidemiologic data implicating a contaminated drug or device used for epidural anesthesia as the likely cause of the outbreak. In addition, our findings show that the benefits of mNGS extend beyond diagnosis of infections to public health outbreak investigation.